FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS ANTROPOMETRI ANAK PENERIMA PENGOBATAN TUBERKULOSIS PARU (Studi di Balai Kesehatan Paru Masyarakat Wilayah Semarang Tahun 2017) - Anggriani Septiana; Suyatno Suyatno; Martha Irene Kartasurya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
In Indonesia tuberculosis case was still high which was 330.910 cases. In Central Java on 2015 7,51% tuberculosis patients were children. The purpose of the research was to analyze factors related to anthropometry status of children with pulmonary tuberculosis medication. Research design was using cross sectional. Anthropometry status was measured using Z score BMI/Age. The research samples were 48 children aged 5-14 years old who got treatment in Semarang Public Pulmonary Health Office and were chosen with total sampling technique. Data was collected using structural interview, and analyzed using Chi Square test and Rank Spearman. The results showed that children whose classified as very thin and thin were 22,9%, level of energy adequacy was 104,42 ± 28,29%, level of protein adequacy was 42,67 ± 15,38%, level of zinc adequacy was 86,23 ± 32,96%, level of iron adequacy was 212,44 ± 213,04%, level of vitamin A adequacy was 242,35 ± 158,47%, level of vitamin C adequacy was 204,24 ± 185,00%, level of vitamin B6 adequacy was 139,88 ± 54,66%. Factors related to anthropometry status score Z BMI/Age of children with pulmonary tuberculosis medication were level of zinc adequacy (r=-0,289; p=0,046), and level of iron adequacy (r=-0,293; p=0,043). Meanwhile, other factors such as father’s education, mother’s education, family economy status, level of energy, protein, vitamin A, C and B6 adequacies were not related to anthropometry status score Z BMI/Age of children with pulmonary tuberculosis medication. It can be concluded that level of zinc and iron adequacies were related to anthropometry status score Z BMI/Age of children with pulmonary tuberculosis medication